The Impact of the Antimicrobial Compounds Produced by Lactic Acid Bacteria on the Growth Performance of Mycobacterium avium subsp. paratuberculosis - Kralik, Petr; Babak, Vladimir; Dziedzinska, Radka (Frontiers in Microbiology, 2018)
Cell-free supernatants (CFS) extracted from various lactic acid bacteria cultures were applied to Mycobacterium avium subsp. paratuberculosis (MAP) cells to determine their effect on MAP viability. In addition, 5% lactic acid (pH 3) and commercially synthetized nisin bacteriocin were also tested. This procedure was chosen in order to mimic the influence of lactic acid bacteria compounds during the production and storage of fermented milk products, which can be contaminated by MAP. Its presence in milk and milk products is of public concern due to the possible ingestion of MAP by consumers and the discussed role of MAP in Crohn’s disease. Propidium monoazide real time PCR (PMA qPCR) was used for viability determination. Although all CFS showed significant effects on MAP viability, two distinct groups of CFS – effective and less effective – could be distinguished. The effective CFS were extracted from various lactobacilli cultures, their pH values were mostly lower than 4.5 and their application resulted in > 2 log10 reductions in MAP viability. The group of less effective CFS were filtered from Lactococcus and enterococci cultures, their pH values were higher than 4.5 and their effect on MAP viability was < 2 log10. Lactic acid elicited a reduction in MAP viability that was similar to that of the group of less effective CFS. Almost no effect was found when using commercially synthetized nisin at concentrations of 0.1 to 1000 µg/ml. A combination of the influence of the type of bacteriocin, the length of its action, bacteriocin production strain and pH are all probably required for a successful reduction in MAP viability. However, certain bacteriocins and their respective LAB strains (Lactobacillus sp.) appear to play a greater role in reducing the viability of MAP than pH.